Optimization of bioconversion of green waste to sugar for ethanol production - Ng, Bernard Jia Han. (2010)
Ethanol production from green waste can be useful in helping solve the current energy crisis, food crisis and climate change. During the bioconversion process, enzymatic hydrolysis, which converts hemicelluloses and celluloses to reducing sugar, was focused on. Hence, the fermentation of reducing sugar to ethanol is more easily carried out once high reducing sugar yield is obtained.